2010
DOI: 10.1371/journal.pgen.1001199
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Guanylyl Cyclase to Chemosensory Cilia Requires the Novel Ciliary MYND Domain Protein DAF-25

Abstract: In harsh conditions, Caenorhabditis elegans arrests development to enter a non-aging, resistant diapause state called the dauer larva. Olfactory sensation modulates the TGF-β and insulin signaling pathways to control this developmental decision. Four mutant alleles of daf-25 (abnormal DAuer Formation) were isolated from screens for mutants exhibiting constitutive dauer formation and found to be defective in olfaction. The daf-25 dauer phenotype is suppressed by daf-10/IFT122 mutations (which disrupt ciliogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 51 publications
6
40
1
Order By: Relevance
“…The mechanisms by which ANKMY2 enhances Shh signaling and by which FKBP38 antagonizes this action of ANKMY2 remain unclear, however. ANKMY2 localizes to cilia and contributes to the intraflagellar transport-independent translocation of guanylyl cyclase in C. elegans (35,36). We confirmed the interaction between ANKMY2 and guanylyl cyclase in mammalian cells (data not shown).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The mechanisms by which ANKMY2 enhances Shh signaling and by which FKBP38 antagonizes this action of ANKMY2 remain unclear, however. ANKMY2 localizes to cilia and contributes to the intraflagellar transport-independent translocation of guanylyl cyclase in C. elegans (35,36). We confirmed the interaction between ANKMY2 and guanylyl cyclase in mammalian cells (data not shown).…”
Section: Discussionsupporting
confidence: 69%
“…9A). Whereas ANKMY2 was previously shown to localize to cilia in C. elegans (35,36), we found that EGFP-ANKMY2 was distributed throughout the cytoplasm of MEFs, with no apparent localization to cilia (Fig. 9B).…”
Section: Untreated Shhcontrasting
confidence: 55%
See 1 more Smart Citation
“…DAF-25 was recently shown to be required to target receptor guanylyl cyclases to sensory cilia in C. elegans (Fujiwara et al, 2010;Jensen et al, 2010), suggesting a possible role in localizing cGMP signaling cascade components. We found that in AWB, TAX-4::GFP localization was unaffected, whereas TAX-2::GFP expression was either lost or restricted to the cell bodies ( Table 2).…”
Section: Other Candidate Proteinsmentioning
confidence: 99%
“…However, there is no evidence for transition zone protein involvement in cGMP signaling. So far, Caenorhabditis elegans DAF-25 (also termed CHB-3; ortholog of mammalian Ankmy2) is the only ciliary protein specifically associated with cGMP signaling (Fujiwara et al, 2010;Jensen et al, 2010). Disrupting DAF-25 results in the failure of two different guanylyl cyclase proteins to target to cilia in sensory neurons.…”
Section: Introductionmentioning
confidence: 99%